2022
DOI: 10.1186/s13102-022-00474-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low back pain on clinical-functional factors and its associated potential risk of chronicity in adolescent dancers of classical ballet: cross-sectional study

Abstract: Background Low back pain (LBP) is a common symptom in classical ballet dancers, which can limit their daily activities and dance training routines. The purpose of the study was to verify the association and comparison of clinical-functional outcomes (spine flexibility and foot posture) between different levels of intensity low back pain in adolescents of classical ballet and the potential risk of chronicity using the STarT back tool. Methods Cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
3
1
Order By: Relevance
“…11,[27][28][29] Furthermore, previous studies have suggested high recruitment of lumbar spine muscles during ballet movements that demand hip and spine hyperextension, and therefore, weak abdominal muscles may negatively affect lumbar flexibility. 27,30,31 No other significant findings were observed in the current study in muscle activation for any other dynamic tasks.…”
Section: Emg Datacontrasting
confidence: 66%
“…11,[27][28][29] Furthermore, previous studies have suggested high recruitment of lumbar spine muscles during ballet movements that demand hip and spine hyperextension, and therefore, weak abdominal muscles may negatively affect lumbar flexibility. 27,30,31 No other significant findings were observed in the current study in muscle activation for any other dynamic tasks.…”
Section: Emg Datacontrasting
confidence: 66%
“…Ballroom dancers, especially females, are often characterized by a slender silhouette, low body weight, and low body fat, which of course may be influenced by the training process requiring high energy expenditure, but may also be affected by high personal standards and desiring low body fat as it is believed to improve performance [16][17][18]. Due to the intensive dance training and complex movement involving jumps, turns and rapid changes in direction, dancers often suffer musculoskeletal injuries and low back pain [19]. The pathogenesis of low back pain in dancers is, however, multifactorial and remains non-specific [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the intensive dance training and complex movement involving jumps, turns and rapid changes in direction, dancers often suffer musculoskeletal injuries and low back pain [19]. The pathogenesis of low back pain in dancers is, however, multifactorial and remains non-specific [19,20]. Some studies suggest that low back pain in dancers may be linked to the postural adjustments resulting from dance practice [19,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation